The Relationship Between Sensation Seeking and Tobacco and Alcohol Use Among Junior High School Students: The Regulatory Effect of Parental Psychological Control - Zhao, Weiguo; Xu, Fei; Ding, Wen; Song, Yining; Zhao, Qi (Frontiers in Psychology, 2019)
The present study primarily aims to examine differences in the use of tobacco and alcohol by junior high school students under different parental control levels (including parental psychological control and parental behavioral control). It thus explores the regulatory effect of parental control on the relationship between adolescent sensation seeking and tobacco and alcohol use. A total of 1,050 junior high school students in Shandong province were surveyed using sensation-seeking scale, parental control scale, and adolescent health-related risk behavior questionnaire. As the results showed, (1) sensation seeking and gender had effects on the use of tobacco and alcohol among junior high school students; (2) parental psychological control can enhance and moderate the relationship between sensation seeking and the use of tobacco and alcohol; (3) parental behavioral control cannot regulate the relationship between sensation seeking and the use of tobacco and alcohol among junior high school students; and (4) no significant urban-rural differences were found regarding the regulatory effects of parental psychological control on sensation seeking and alcohol and tobacco use in junior high school students.